Bismuth-argentum alloys as alternative high temperature lead-free solder - Rosilli, Rohaizuan (2012)
Solder reaction is one of the oldest metallurgical processes for joining metal parts. Today, the use of solder in modern microelectronic technology is ubiquitous. Lead solder has been widely used in the semiconductor industry for a long time. However,despite the long term acceptance of lead by human society, lead poisoning is known well health treat. The common types of lead poisoning may be classified as alimentary,neuromotor and encephalic. Although Tin-Lead (Sn-Pb) can be replaced by lead free solder for low temperature applications, but there is no lead free solder available in the market that can replace the high temperature leaded solders. Most of the internal joining such as in first level interconnection flip chip is using 90-95 weight percent of lead. Stated in the RoHS (The Restriction on the Use of Hazardous Substances) regulation, the law gave exemptions to the industry by allowing the use of solder with above 85 weight percent of lead. Despite numerous studies on lead free solders in recent years there are only limited number of reports and journal on the research and development for high temperature lead free alternative solders. High temperature lead free soldering is a key technology for electronic components and assemblies, and requires a high level of process control. This technology can provide value-added characteristics to the products, including excellent heat conductivity and high reliability. High lead-bearing solders are still in use and hinder the recycling of consumer electronic products even though the circuit boards are assembled with intermediate temperature range lead free solder such as Tin-Silver-Copper (Sn-Ag-Cu). Tin-Antimony (Sn-Sb) and Sn-Sb based alloys are promising lead free solders for high temperature application. This is especially true of Tin-5Antimony (Sn-5Sb) because the melting point range is 234 ⁰C to 240 ⁰C. However the melting point is not above 260 ⁰C to enable it in replacing Lead-10Tin (Pb-10Sn). Thus, the establishment of high temperature lead free solders or other interconnection technologies is an urgent priority in the electronics industry. In this research, three samples of Bismuth-Silver (Bi-Ag) alloys with different compositions were investigated using Differential Scanning Calorimetry (DSC) to check their melting point. For Sample 1 Bismuth-1.5Silver (Bi-1.5Ag), Sample 2 Bismuth-2.5Silver (Bi-2.5Ag) and Sample 3 Bismuth-3.5Silver (Bi-3.5Ag) are produced by using casting process. This research carried out some testing to compare their characteristics and properties such as comparison of Copper (Cu) grooving, Copper (Cu) grooving thickness, Copper-rich (Cu-rich) particles size in solder bulk and wetting angle using Optical Microscope in terms of cross sectional area. The area elemental analyses were carried out using Scanning Electron Microscope-Energy Dispersive X-ray (SEM-EDX). Mechanical grooving appeared in all samples and no intermetallic compound (IMC) formed at the interface for first reflow, second reflow and third reflow process. Sample 3 that contain higher wt% of Ag is better compared to Sample 2 and Sample 1 because it increases the melting point, have greater Copper (Cu) grooving, give higher average of Copper-rich (Cu-rich) particles size and lower wetting angle. Third reflow process gives higher Copper (Cu) grooving and give a higher Copper-rich (Cu-rich) particles size average. But, it lowers the wetting angle value.